2017
DOI: 10.1111/jocn.13932
|View full text |Cite
|
Sign up to set email alerts
|

Optimising implementation of a patient‐assessment framework for emergency nurses: A mixed‐method study

Abstract: Aims and objectives: To determine potential facilitators and barriers and tailor interventions to optimise future implementation of a patient-assessment framework into emergency nursing practice. Design: A mixed-method convergent study design was used.Methods: Thirty eight early career emergency nurses from five Australian hospitals participated in an education workshop on the HIRAID assessment framework. Simulated clinical scenarios enabled participants to experience conducting a patient assessment with and w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 39 publications
1
18
0
Order By: Relevance
“…These findings are consistent with other studies showing that a lack of awareness of guidelines or perceived lack of evidence for measurable change represent a barrier to CP implementation [45,47,48]. Other researchers have highlighted the importance of developing educational material for clinical personnel [43], designing innovative strategies to optimize clinician education in high stress and fast-paced settings [41], and focusing on training and education as key intervention functions for enabling behaviour change [39,40].…”
Section: Knowledge Dissemination and Aligning Informationsupporting
confidence: 87%
See 1 more Smart Citation
“…These findings are consistent with other studies showing that a lack of awareness of guidelines or perceived lack of evidence for measurable change represent a barrier to CP implementation [45,47,48]. Other researchers have highlighted the importance of developing educational material for clinical personnel [43], designing innovative strategies to optimize clinician education in high stress and fast-paced settings [41], and focusing on training and education as key intervention functions for enabling behaviour change [39,40].…”
Section: Knowledge Dissemination and Aligning Informationsupporting
confidence: 87%
“…While this study was not intended to systematically identify intervention functions or behaviour change techniques as some studies have done according to the Behaviour Change Wheel (BCW) framework [39][40][41][42], we found that by adopting the TDF as an analytical framework, we were able to successfully identify the facilitators and barriers that would impact the implementation of a CP for pediatric concussion in emergency departments. The 6 clusters of TDF domains identified in the interviews each reflect 2-4 predominant concerns that can be condensed into six overarching themes regarding clinicians' views on the implementation of a CP.…”
Section: Discussionmentioning
confidence: 99%
“…This paper illustrates the use of validated frameworks of behaviour change to identify facilitators and barriers and select implementation strategies for the implementation of a blunt chest injury care bundle . This paper adds to researcher experiences of the prospective use of the TDF and Behaviour Change Wheel as a theory-based implementation strategy in emergency care [7, 12, 32, 3639]. This paper provides a worked example of the use of the TDF and Behaviour Change Wheel used together systematically to identify facilitators and barriers and derive implementation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Implementation strategies need to support individual practitioners, managers, and understand the context as well as receive strong organisational support and patronage which is in uential to normalising a new practice among staff 23 . An evidence informed and context speci c implementation strategy is essential to sustained, reliable and high uptake 16,24 . While education and training is accompanied by associated cost, this study has shown that HIRAID can lead to signi cant cost bene ts and pay back for an organisation.…”
Section: Discussionmentioning
confidence: 99%